2023
DOI: 10.1111/nph.19003
|View full text |Cite
|
Sign up to set email alerts
|

Phloem development

Abstract: The evolution of the plant vascular system is a key process in Earth history because it enabled plants to conquer land and transform the terrestrial surface. Among the vascular tissues, the phloem is particularly intriguing because of its complex functionality. In angiosperms, its principal components are the sieve elements, which transport phloem sap, and their neighboring companion cells. Together, they form a functional unit that sustains sap loading, transport, and unloading. The developmental trajectory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 148 publications
0
8
0
Order By: Relevance
“…It is still unclear what CANAR’s role in the xylem is. Water exchange between the xylem and phloem is necessary to load and transport phloem content ( 2 ). Xylem-expressed CANAR could potentially help to facilitate this exchange.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still unclear what CANAR’s role in the xylem is. Water exchange between the xylem and phloem is necessary to load and transport phloem content ( 2 ). Xylem-expressed CANAR could potentially help to facilitate this exchange.…”
Section: Discussionmentioning
confidence: 99%
“…The phloem route transports carbon assimilates, amino acids, RNAs, and hormones from source tissues (e.g. mature leaves) into sink tissues (such as juvenile leaves, roots, meristems, and reproductive organs) ( 1 , 2 ). The hydrostatic pressure differences between source and sink drive the flow of the phloem content ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis mrf1 mutants have shown the delayed flowering phenotype and, conversely, MRF1 -overexpressing plants exhibited early flowering [ 45 ]. It has been reported that the maturity of the phloem affects the transportation of water and nutrients in plants, which could impact their growth and flowering [ 46 ]. The more mature the phloem is, the more effectively the plants are able to transport water and nutrients to the growing parts, which could promote plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…The main function of vascular tissue include transport of water, ions, photoassimilates and other nutrients (Hardtke 2023). Bundle sheath cells, which surround vascular bundle, are specialized in the water transport and sulfur transport in rice (Lei Hua 2021), or glucosinolate biosynthesis and sulfur in Arabidopsis (Sylvain Aubry 2014).…”
Section: Introductionmentioning
confidence: 99%